Evaluation of the Effects of 1,25VitD3 on Inflammatory Responses and IL-25 Expression - Li, Nana; Saghafi, Nafiseh; Ghaneifar, Zahra; Rezaee, Seyed Abdorahim; Rafatpanah, Houshang; Abdollahi, Elham (Frontiers in Genetics, 2021)
Abstract VitD3 may contribute to a successful pregnancy through modulation of immune responses, so VitD3 deficiency may have a role in the immunopathogenesis of unexplained recurrent spontaneous abortion (URSA). However, the mechanisms of immunomodulatory actions of VitD3 in decreasing the risk of recurrent spontaneous abortion have not been understood well. Objective: The purpose of this research was to investigate the influence of 1,25VitD3 on IL-25 and related cytokines of Th17 cells including, IL-17A, IL-6, and IL-23 in peripheral blood mononuclear cells of healthy women as a control group and women with unexplained recurrent spontaneous abortion. Method: Isolation of peripheral blood mononuclear cells (PBMCs) was performed from peripheral blood of the subjects of the studied groups (20 women with URSA as a case group, and 20 control women). The effects of 1,25VitD3 (50 nM, for 24 hours) on the studied parameters were evaluated and were compared to the positive and negative controls in vitro. Flow cytometry analysis was used to determine the percentages of regulatory T cells and Th17 cells. For gene expression measurement and cytokines assay, Real-time PCR and ELISA were carried out. Results: The proportion of Th17 cells in women with URSA was considerably higher than in the control group. IL-25 mRNA and protein levels in cultured PBMCs from women with URSA were lower than the controls. 1,25VitD3 increased IL-25 expressions at both the protein and mRNA levels in PBMCs from women with URSA relative to the control group. Additionally, 1,25VitD3 treatment not only significantly decreased the percentage of Th17 cells frequency but also reduced expressions of IL-6, IL-17A, and IL-23 in PBMCs from women with URSA. Conclusion: 1,25VitD3 may diminish inflammatory responses cells via downregulating of IL-25 expression. It could be an interesting subject for future researches in the field of the immunopathology of URSA to identify molecular pathways in URSA treatment.